An analysis of the effectiveness of corporate social responsibility in establishing brand loyalty - Case of Delta Beverages-Chibuku. - Moyo, Duduzile (Midlands State Univeristy, 2017)
The main purpose for this research was to analyze the effectiveness of corporate social responsibility in establishing brand loyalty and the company under study was Delta Beverages-Chibuku. Literature was reviewed through the use of text books, previous thesis and different articles journals. The major driving force for this study was the stiff competition being faced by the Chibuku brand products resulting in a decrease in market share. Descriptive research and exploratory research designs were used to gather the relevant data from the company’s employees, management and customers. A sample size totalling 97 respondents was used.For data collection structured interviews were used for management and questionnaires for customers. The response rate was 69%. Respondent selection was through the use of probability sampling techniques thus simple random sampling and stratified random sampling. The evaluation was brought out and the major findings discussed. The hypothesis results indicated that sponsorships and donations were effective in establishing brand loyalty hence rejecting the null hypothesis, waste recycling statistical test results showed that waste recycling was not effective in establishing brand loyalty thus the null hypothesis was accepted. The researcher concluded that sponsorships and donations were effective in establishing brand loyalty and waste recycling was ineffective leading to recommending the organization to participate more in community based initiatives, being active in the sponsoring of other sporting events other than soccer and also communicate waste recycling strategies to their customers.